Immunoprecipitation Strategies to Isolate RIPK1/RIPK3 Complexes in Mouse Macrophages. Issue 6 (9th June 2021) - Siokas, Ioannis; Zhang, Dingqiang; Poltorak, Alexander; Muendlein, Hayley; Degterev, Alexei
Abstract: A large protein complex, containing RIPK1, RIPK3, and caspase‐8 and known as Complex II, has emerged as one of the key mediators of cell death downstream from a range of innate immune triggers. This regulatory mechanism plays a prominent role in macrophages, where Complex II has been linked to apoptosis, pyroptosis, and necroptosis as well as the enhancement of inflammatory gene expression. Although core components of this complex are fairly well understood, more subtle proteomic changes that determine the direction of a response once the complex is assembled remain much less clear. In addition, Complex II components undergo a wealth of post‐translational changes that modify the functions of the complex components. This necessitates development of robust and efficient methods of isolating Complex II for further interrogation of its composition and the post‐translational modifications of its components. This article describes several methods that we have developed for Complex II isolation, which can be used to obtain complementary information about this signaling mechanism. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Isolation of Complex II in necroptotic and pyroptotic macrophages using FADD immunoprecipitation Basic Protocol 2 : Isolation of the complexes formed by the conditionally expressed 3XFLAG‐RIPK1 protein Alternate Protocol : Alternative methods of immunoprecipitation of RIPK1 and other Complex‐II‐related factors Support Protocol : Generation of stable macrophage cell lines using lentiviral expression Basic Protocol 3 : Use of proximity labeling to identify necrosome components in the detergent‐insoluble fraction of the cell lysates